TPACK-based professional development on web 2.0 for Spanish teachers: a case study. Issue 4 (3rd May 2020) - Bustamante, Carolina
Abstract: The topic of this study is professional development (PD) on Web 2.0 technologies for foreign language teachers and integration of these tools into the language classroom. This research explored the experiences of eighteen teachers of Spanish in grades 7-12 from both rural and urban areas in Nebraska, United States, who participated in a technology, pedagogy, and content-based online PD. This qualitative case study included data from interviews, classroom observations, and documents to explore the learning and integration journeys of Spanish teacher participants during and after the PD. While qualitative findings indicated mainly positive learning experiences in the three areas -technology, pedagogy, and content- as well as in technology integration, the observational data illuminated issues of technology access and use of the target language (TL) by the teachers. The article concludes with implications for the design of PD on technology for foreign language teachers.